Data-Driven Company Registry : Guidance Note - World Bank (Washington, DC, 2022)
The accelerated expansion of digital economy ecosystems mandates company registries to digitalize and connect to these ecosystems responding to new business dynamics. Achieving data-driven company registries requires considerable effort to improve data management. Some jurisdictions achieved significant automation of company registration procedures through digitalization. Real-time company registration requires fraud prevention mechanisms. Significant levels of simplification of company registration and removal of in-person interactions require improvement in fraud prevention and detection. The digitalization of a company registry requires a seamless cross-border digital identity. Jurisdictions are looking to simplify the onboarding for digital identity and the requirements for digital signature in the company registration procedures. Making company registration accessible for domestic and foreign founders and investors has become a mandatory improvement. Recent solutions involve the use of blockchain for digital business identity and online onboarding using biometrics and AI/machine learning for identity validation. Furthermore, some initiatives at the regional level aim to interconnect national business registers belonging to a region, allowing business intelligence through cross-border comparability of data and improving access to information on companies in a cross-border context.